Cracking the new GRE, with DVD - Pierce, Douglas; Princeton Review (Firm); Random House (Firm) (New York : Random House, 2011)
Presents a guide to assist with preparation for the new GRE, with practice questions pertaining to the verbal, math, and analytical writing sections; tips, techniques, and detailed explanations for answers; and access to four full-length practice tests.
At head of title: The Princeton Review.
Statement of responsibility from cover.
"Revised & updated for the new test"--Cover.
Keywords: Graduate Record Examination -- Study guides; Universities and colleges -- Graduate work -- Examinations -- Study guides